Reconstruction of Marine Pollution Regulations and Control of Plastic Waste in The Indonesian Sea in The Context of Biodiversity Protection - Nurhayati, Ema (Civiliza Publishing, 2025)
This research examines the issue of Marine Pollution in Indonesia, which is the second largest contributor of plastic waste in the world with an estimated 3.22 million tons of plastic waste entering marine waters annually. The research aims to analyze the reconstruction of regulations controlling plastic waste in the sea for the protection of biodiversity. Using a normative legal research method with statutory and conceptual approaches, this research identifies gaps in Indonesia's Marine Pollution control regulatory framework. The results show fragmentation of regulations and overlapping authority between institutions, as well as significant impacts on marine biodiversity affected by plastic waste. This research proposes a regulatory reconstruction model comprising five main strategies: harmonization of regulations through the establishment of a specific Law on Marine Pollution Control, institutional strengthening through a Marine Pollution Prevention Coordination Agency, diversification of regulatory instruments including economic instruments, law enforcement reform, and strengthening multi-stakeholder participation. Implementation of this model is expected to increase the effectiveness of plastic waste control in Indonesian seas for the protection of marine biodiversity.